2020
DOI: 10.15835/nbha48311959
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phytochemical characterization of F1 Streptocarpus hybrids and antioxidant potential of their flower extracts

Abstract: Streptocarpus x hybridus is a very popular houseplant with colourful flowers arousing thus the interest of plant breeders. Its potential value is even higher since different chemical compounds could be identified and used for food and pharmaceutical industries. Therefore, the objectives of this study were: to determine genetic relationships between twelve F1 Streptocarpus hybrids and their genitors; to determine the total phenolic and flavonoid content; to evaluate the antioxidant activity of the analysed indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…The potential value of Streptocarpus may be much higher than its exclusive use as an ornamental plant. As reported by Hârţa et al [13], a variety of chemical compounds can be identified in its tissues, which can be applied in the food and pharmaceutical industries. For example, Streptocarpus flowers can be an important source of antioxidants.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The potential value of Streptocarpus may be much higher than its exclusive use as an ornamental plant. As reported by Hârţa et al [13], a variety of chemical compounds can be identified in its tissues, which can be applied in the food and pharmaceutical industries. For example, Streptocarpus flowers can be an important source of antioxidants.…”
Section: Introductionmentioning
confidence: 91%
“…A shoot height at a statistically high level was also obtained under the influence of red light (R-5.83), red with blue (RB-5.33), the addition of green (RBG-5.47) LED and under fluorescence (Fl-6.53). In the studies carried out to date on plant in vitro cultures of Streptocarpus by various authors, there have been no reported studies that have examined the effect of different quality of LED light on its developmental parameters [13,[35][36][37]. Moreover, as for the in- In the studies carried out to date on plant in vitro cultures of Streptocarpus by various authors, there have been no reported studies that have examined the effect of different quality of LED light on its developmental parameters [13,[35][36][37].…”
Section: Biometrical Observationsmentioning
confidence: 99%
See 2 more Smart Citations